WATER LEVEL MEASUREMENT VIA POLYMER DIAPHRAGM AND FIBER BRAGG GRATING SENSOR (Jurnal Teknologi (Sciences & Engineering), 2016)
In this paper, a new design of sensor head to monitor water level inside the tank based on fiber Bragg grating (FBG) was demonstrated. The sensor head consisted of an FBG placed under a very thin polymer plastic sheet layer. This sensor head acts as a sensitive diaphragm to sense water level based on hydrostatic pressure caused by the liquid weight. The hydrostatic pressure imposed on the sensor head produced strain in the embedded FBG, which caused a shift in Bragg wavelength detected by the optical spectrum analyzer. A calibration curve to relate liquid level and shift in the Bragg wavelength was constructed. A linear relationship between the shift in Bragg wavelength and the water level up to 70 cm height with a sensitivity of 2 pm/cm is achieved in this work.